The Paradigm of Finnish Reviews of "Without Dogma" by Henryk Sienkiewicz: Observations on the Issue of Intercultural Communication and the Functioning of Common Motifs of European Culture - Krzysztof Stępnik (Acta Baltico-Slavica, 2021)
The Paradigm of Finnish Reviews of Without Dogma by Henryk Sienkiewicz: Observations on the Issue of Intercultural Communication and the Functioning of Common Motifs of European Culture